Comparison of psychological interventions for anxiety, depression, fatigue and quality of life in colorectal cancer survivors: A systematic review and network meta-analysis protocol. - Yujie Liang; Xu Zhang; Shan Li; Zhiwen Wang (PLoS ONE)
Background Previous studies have found that psychological interventions have a positive effect on improving physical and psychological problems in colorectal cancer survivors. However, there is still a lack of high-quality evidence reviews that summarize and compare the impact of different psychological interventions. The aim of this study was to synthesize existing psychological interventions and use network meta-analysis to explore whether psychological interventions improve anxiety, depression, fatigue and quality of life in colorectal cancer (CRC) survivors. Methods We will extract relevant randomized controlled trials of psychological interventions for CRC survivors from eight electronic databases, including PubMed, Embase, The Cochrane Library, Web of Science, CINAHL, PsycInFO, CNKI, and Wanfang database. Two reviewers will independently screen the literature and extract data. The risk of bias of the included studies will be assessed using the RoB2: Revised Cochrane Risk of Bias Tool. We will then conduct paired meta-analyses and network meta-analyses of the extracted data, using a frequency-based framework and random effects models. Discussion To the best of our knowledge, this study is the first proposed qualitative and quantitative integration of existing evidence using systematic evaluation and network meta-analysis. This study will inform health policy makers, healthcare providers' clinical intervention choices and guideline revisions, and will help to reduce depression and anxiety in CRC survivors, reduce fatigue, improve quality of life.